France's response to the Ivorian crisis under Gbagbo through the lens of IR regime theory - Bovcon, M (2012)
There exists a certain consensus among scholars and French diplomats that the golden era of the exceptionally close and amicable relations between France and its former sub-Saharan colonies is over. Nevertheless, the conclusions that these researchers arrive at regarding the current state of France’s African policy are rather different. The aim of the thesis is to determine which of the three paradigms concerning France’s African policy – the incremental adaptation, normalisation or confusion – best describes the French response to the crisis in Côte d’Ivoire under the Gbagbo regime. The contribution of the thesis is the analysis of continuities and changes of this specific Franco-African relationship, also known as Françafrique, within the framework of international relations regime theory. The thesis argues that France’s diplomacy towards the Ivorian crisis and her role in the multilateral conflict resolution strategy, reveal her growing inability to defend the constitutive principle of the Françafrique regime: grandeur. Her pursuit of middle power status through maintaining hegemonic relations to her favourite former colony was considerably challenged by various domestic and systemic factors, among which the Ivorian power struggles and Gbagbo’s duplicitous politics played a considerable part. Moreover, the thesis also points to the persistence of some old rules and decision-making procedures of the Françafrique regime, especially the resilience of informal networks. These old practices collide with France’s growing desire to make her African policy more transparent, coherent and efficient. It is therefore concluded that the coexistence of these opposite tendencies in France’s response to the Ivorian crisis under Gbagbo, as well as the inconsistent resort to the Françafrique principle, rules and decision-making procedures are best explained by the confusion paradigm of France’s African policy.